The sociological determinants of scientific bias. Issue 1 (2nd January 2022) - Michalski, Joseph H.
ABSTRACT: Science is an ethical community whose practitioners aim to discover information about the natural world and to explain discernible patterns that might be detected. Those who pursue science generally embrace certain epistemic values that help establish the moral boundaries of the community, while the twin pillars of rationality and empiricism serve as the foundations upon which scientists establish their truth claims. Yet however robust the assertions might appear, they nevertheless are the by-products of an exclusively human endeavor directly impacted by those sociological forces that apply throughout the social universe, including the scientist's social location and the importance of enhancing one's reputation. The current paper identifies key sociological factors that help shape scientific bias and the nature of the justifications used to defend truth claims. A case study of one community committed to a sociological paradigm demonstrates the utility of the explanatory framework advanced. A more self-conscious awareness of the forces at play that create such biases can help mitigate their deleterious impacts that subvert the quest for explanatory knowledge and valid truth claims about observable phenomena.